Pertukaran Peran Suami-Istri dan Implikasinya Terhadap Waris Perspektif Maqāṣid Al-Syarī‘ah - Sukarman Sukarman; Abdul Hadi (Syariati: Jurnal Studi Al-Qur'an dan Hukum, 2019)
This paper reviews three main things in families that have integral-functional traits (childcare, livelihood and inheritance). Paradigm of conventional Islamic law divides the role between husband and wife rigidly. for example, living is the duty ofa husband, caring for children is the duty of the wife, and inheritance rights are legal 2 : 1 for husband and wife. With the occurrence of social change that has caused a change in the role of husband and wife both in the form of division of rolesand even the exchange of roles between husband and wife. This is certainly not fair when there is no balance between rights and burden carried out, so we need a fair legal solution. There fore this study analyzes the problem using the perspective of maqâṣid asy-syarî‘ah.